2018
DOI: 10.1007/s10072-018-3480-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia influenced malnutrition in Parkinson’s disease patients

Abstract: PD patients are at a risk of hyperhomocysteinemia. Regular physical activity decreases Hcy level, whereas poor motor function increases it. There is correlation between Hcy level and malnutrition in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Third, in the present study, lower numbers of regular exercise habits were observed in the malnutrition-risk group relative to the normal-nutrition group. However, regular physical activity could decrease the homocysteine levels [ 49 ], which are significantly associated with nutritional status in PD patients [ 50 ]. In addition, increasing levodopa (L-dopa) equivalent daily dosages were associated with an increasing probability of malnutritional risk in PD patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, in the present study, lower numbers of regular exercise habits were observed in the malnutrition-risk group relative to the normal-nutrition group. However, regular physical activity could decrease the homocysteine levels [ 49 ], which are significantly associated with nutritional status in PD patients [ 50 ]. In addition, increasing levodopa (L-dopa) equivalent daily dosages were associated with an increasing probability of malnutritional risk in PD patients [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Many risk factors may lead to depressive disorders, such as gender, age, co-occurrence with other mental disorders, cardiovascular disease and increased chemical compounds that perturb neurotransmitters. [3][4][5] Homocysteine is an α-amino acid derived from heating methionine with sulphuric acid, 6 and the chemical structure of homocysteine is similar to cysteine. 7 Elevated plasma homocysteine, also known as hyperhomocysteinaemia, may be a risk factor for cardiovascular diseases, Parkinson's disease and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] It is also associated with neurodegenerative and psychiatric disorders, such as Alzheimer's disease, schizophrenia and anxiety. 12,13 Hyperhomocysteinaemia can be caused by impaired renal function, smoking, lack of physical activity, high blood pressure and hyperlipidaemia since some lipid-lowering drugs might also have an effect on homocysteine levels, 6,12,14 whilst excessive alcohol intake, high coffee intake and vitamin B12 and folate deficiency may increase the risk of hyperhomocysteinaemia. 6 Accordingly, supplementation with either folic acid or vitamin B12 has been proposed for the treatment of hyperhomocysteinaemia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homocysteine (Hcy) is a non-protein amino acid, formed by methionine (Met) derived from the diet and secreted during metabolism 1 . An elevated level of Hcy in the blood results in hyperhomocysteinemia (HHcy) and is closely associated with some neurodegenerative diseases, including dementia, Alzheimer's disease and Parkinson's disease 2 - 5 . The deleterious influences of HHcy have also been reported in the developing central nervous system (CNS) 1 , 6 .…”
Section: Introductionmentioning
confidence: 99%